2015
DOI: 10.1017/dmp.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Legal Protections to Promote Response Willingness Among the Local Public Health Workforce

Abstract: Specific legal protections augment a majority of LHD workers' response willingness. Policymakers must, however, balance improved response willingness with other considerations, such as the ethical implications of prioritizing responders over the general public. (Disaster Med Public Health Preparedness. 2015;9:98-102).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…This suggests that, whenever possible, LHDs should devote resources to securing vaccines and/or countermeasures for staff and their families. 16 Plans for providing vaccines to staff and families during a more common infectious disease response (e.g., seasonal influenza) may differ from those for emerging infectious diseases. 17 Once LHDs commit to protecting staff and their families with vaccines and countermeasures, they should consider how different infectious disease scenarios might impact access and distribution of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, whenever possible, LHDs should devote resources to securing vaccines and/or countermeasures for staff and their families. 16 Plans for providing vaccines to staff and families during a more common infectious disease response (e.g., seasonal influenza) may differ from those for emerging infectious diseases. 17 Once LHDs commit to protecting staff and their families with vaccines and countermeasures, they should consider how different infectious disease scenarios might impact access and distribution of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that over 75% of LPHA workers would be more willing to respond across a range of emergency scenarios if they were guaranteed access to personal protective equipment (PPE). 17 The availability of PPE helps to ensure safety at work, and effective use of PPE depends upon proper training. Similarly, our study found that provision of training and perceived safety at work were both associated with a significantly greater odds of LPHA workers' WTP in DR efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate that the availability of specific types of support during future DR activities influences LPHA workers’ WTP in these efforts. Prior research has found that over 75% of LPHA workers would be more willing to respond across a range of emergency scenarios if they were guaranteed access to personal protective equipment (PPE) 17 . The availability of PPE helps to ensure safety at work, and effective use of PPE depends upon proper training.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data suggest that, if LHDs took certain steps such as guaranteeing access to and training about PPE, response willingness might increase. 8 As training is essential to employees' capacity to fulfill their responsibilities during an emergency, trainings and drills should be offered during standard work hours. Employees should not be expected to participate in trainings outside of their standard work week (e.g., at night, on the weekend).…”
Section: Respect For Persons Building Capacitymentioning
confidence: 99%